Association of Dapagliflozin vs Placebo With Individual Kansas City Cardiomyopathy Questionnaire Components in Patients With Heart Failure With Mildly Reduced or Preserved Ejection Fraction: A Secondary Analysis of the DELIVER Trial - Peikert, Alexander; Chandra, Alvin; Kosiborod, Mikhail N; Claggett, Brian L; Desai, Akshay S; Jhund, Pardeep S; Lam, Carolyn S P; Inzucchi, Silvio E; Martinez, Felipe A; de Boer, Rudolf A; Hernandez, Adrian F; Shah, Sanjiv J; et al. (JAMA cardiology, 2023)
IMPORTANCE: Dapagliflozin has been shown to improve overall health status based on aggregate summary scores of the Kansas City Cardiomyopathy Questionnaire (KCCQ) in patients with heart failure (HF) with mildly reduced or preserved ejection fraction enrolled in the Dapagliflozin Evaluation to Improve the Lives of Patients With Preserved Ejection Fraction Heart Failure (DELIVER) trial. A comprehensive understanding of the responsiveness of individual KCCQ items would allow clinicians to better inform patients on expected changes in daily living with treatment. OBJECTIVE: To examine the association of dapagliflozin treatment with changes in individual components of the KCCQ. DESIGN, SETTING, AND PARTICIPANTS: This is a post hoc exploratory analysis of DELIVER, a randomized double-blind placebo-controlled trial conducted at 353 centers in 20 countries from August 2018 to March 2022. KCCQ was administered at randomization and 1, 4, and 8 months. Scores of individual KCCQ components were scaled from 0 to 100. Eligibility criteria included symptomatic HF with left ventricular ejection fraction greater than 40%, elevated natriuretic peptide levels, and evidence of structural heart disease. Data were analyzed from November 2022 to February 2023. MAIN OUTCOMES AND MEASURES: Changes in the 23 individual KCCQ components at 8 months. INTERVENTIONS: Dapagliflozin, 10 mg, once daily or placebo. RESULTS: Baseline KCCQ data were available for 5795 of 6263 randomized patients (92.5%) (mean [SD] age, 71.5 [9.5] years; 3344 male [57.7%] and 2451 female [42.3%]). Dapagliflozin was associated with larger improvements in almost all KCCQ components at 8 months compared with placebo. The most significant improvements with dapagliflozin were observed in frequency of lower limb edema (difference, 3.2; 95% CI, 1.6-4.8; P < .001), sleep limitation by shortness of breath (difference, 3.0; 95% CI, 1.6-4.4; P < .001), and limitation in desired activities by shortness of breath (difference, 2.8; 95% CI, 1.3-4.3; P < .001). Similar treatment patterns were observed in longitudinal analyses integrating data from months 1, 4, and 8. Higher proportions of patients treated with dapagliflozin experienced improvements, and fewer had deteriorations across most individual components. CONCLUSIONS AND RELEVANCE: In this study of patients with HF with mildly reduced or preserved ejection fraction, dapagliflozin was associated with improvement in a broad range of individual KCCQ components, with the greatest benefits in domains related to symptom frequency and physical limitations. Potential improvements in specific symptoms and activities of daily living might be more readily recognizable and easily communicated to patients. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT03619213.
Keywords: senioři; činnosti denního života; kardiomyopatie; Stroke Volume; Dyspnea; průzkumy a dotazníky; mužské pohlaví; funkce levé komory srdeční; Activities of Daily Living; kvalita života; tepový objem; ženské pohlaví; Humans; Surveys and Questionnaires; Cardiomyopathies; srdeční selhání; dyspnoe; Kansas; Female; Aged; Quality of Life; Heart Failure; lidé; Male; Ventricular Function, Left